Students' Responses and Perceptions in Learning Strategy of Ilmu al-Badi Based on Mind Maps l Istijabat al-Talabah wa Tasawuratihim fi Tatbiq Istiratijiyyah Ta’lim ‘Ilmi al-Badi’ al-Qaimah ‘ala al-Kharait al-Dzihniyyah - Hamzah, Hamzah; Fattah, Abd.; Khaira, Boukhari (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
The Learning situation during the pandemic of Covid-19 was very concerning and giving impact on students' understanding. Mind Map strategy is one of the most effective ways to streamline and improve the quality of learning. This study aimed to determine the extent to which students' responses and perceptions in implementing mind map-based Arabic language learning strategies for students of the Arabic Language and Literature Department fifth semester of Sekolah Tinggi Agama Islam Negeri Majene, West Sulawesi. This research was classified as a quantitative research with a survey research design. The data source for this research was students of the Department of Arabic Language and Literature in the fifth semester of Sekolah Tinggi Agama Islam Negeri Majene, West Sulawesi. The data collection was carried out through interviews with respondents and using a questionnaire which was distributed to respondents after learning using the mind map strategy. The data analysis used was descriptive and a Likert scale was used to measure and to identify qualitative and quantitative data. The results of this study were students' responses to the learning strategies of ilmu Badi' based on mind maps increased their grade significantly.  Student's perception of the learning strategy stated they understood the material easier, more efficient, and more enjoyable. They were given time to understand the material. These results confirmed the previous studies results and became recommendation about the application of a Mind Map strategy in learning which was efficient and able to increase students' understanding.